The Influence of Psycho-Educational Therapy on Anxiety in Children with Cancer Undergoing Chemotherapy - Megasari, Anis Laela; Wulandari, Ika Subekti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Cancer is still a significant health problem that causes a high mortality rate worldwide. It affects not only adults but also children. One of the types of cancer commonly suffered by children is leukemia. Chemotherapy is one of the treatments for leukemia. Unfortunately, chemotherapy often leads to issues in children, such as anxiety. This aimed to determine the influence of psycho-Education on anxiety in children with leukemia undergoing chemotherapy. This method using a pre-experimental design with one group pretest posttest. The sample was obtained using total sampling, consisting of 25 respondents. Psycho-educational therapy was conducted three times, and it consisted of four sessions in each activity, namely: Session 1 (education about cancer and treatment therapy), Session 2 (effects of chemotherapy), Session 3 (actions and prevention of chemotherapy side effects), and Session 4: stress management (teaching various non-pharmacological stress management techniques). The intervention was administered three times before the scheduled chemotherapy for 15 minutes. The researcher used Anxiety test by using the Spence Children's Anxiety Scale (SCAS). Results: The Wilcoxon test results showed a p-value of 0.001. Based on the research findings, it indicated that there is an influence of Psycho-Educational Therapy on anxiety in children with leukemia undergoing chemotherapy.